Penerapan Model Pembelajaran Two Stay Two Stray berbasis budaya Tudang Sipulung untuk meningkatkan komunikasi matematis siswa SMP Negeri 5 Labakkang - Rahma Azhary (STKIP Andi Matappa, 2022)
RAHMA AZHARY, 2022. Penerapan Model Pembelajaran Two Stay Two Stray berbasis budaya Tudang Sipulung untuk meningkatkan komunikasi matematis siswa SMP Negeri 5 Labakkang. Skripsi. Dibimbing oleh Rahmat Kamaruddin, dan Vivi Rosida, Program Studi Pendidikan Matematika STKIP Andi Matappa Pangkep. This study aims to determine whether the application of the Two Stay Two Stray Learning Model based on the Tudang Sipulung culture can improve students' mathematical communication at SMP Negeri 5 Labakkang. The main problem of this research is: Can the application of the Tudang Sipulung culture-based Two Stay Two Stray Learning Model improve students' mathematical communication? This type of research uses a descriptive quantitative research type. The population in the study were all students of class VII.A SMP Negeri 5 Labakkang. The results of the descriptive statistical analysis show that the average score of the mathematical communication test results before the implementation of the Two Stay Two Stray learning model based on the tudang sipulung culture is 36.14 with a standard deviation of 12.045, while the average score of students' mathematical communication test results after the application of the Two Stay Two Stray learning model based on tudang sipulung culture is 70.09 with a standard deviation of 16.224. the results of inferential statistical analysis using the t test using the paired sample t test obtained t count -11.317 <t table 2.51765 which means that there are differences in the results of students' mathematical communication tests before and after the application of the Two Stay Two Stray learning model based on tudang sipulung culture with normally distributed data using the Kolmogorof-Smirnov test. Furthermore, the N-Gain test was obtained at 0.51 which indicates that it is in the high interval category, namely g> 0.7 so that it can be said that the application of the Two Stay Two Stray learning model based on tudang sipulung culture can improve students' mathematical communication.